تەریقەتی سۆفیگەریی سەفەوی و هەنگاونان بۆ دامەزراندنی دەوڵەت ( 851 -907 ک/١٤٤٨-١٥٠١ز ) - ئەنوەر, پ.د.كەیوان ئازاد; جبار, سەركۆ ناجی (Sulaimani Journal for Humanities, 2023)
The roots of the Safavids go back to Sheikh Safi Ad-Din Ishaqi Al-Ardabili; he was a Sunni who followed the Shafii School. During the reign of his grandson Ali Siaposh, the first signs of the Shi'ite sect appeared in the Safavid order. The movement towards a Shi'ite political movement was openly carried out during Junaid's reign. And then during the reign of Haidar, the Safavid movement took a step forward when he organized his followers, and his followers were known as (Qizilbash). Haider kept trying to gain power and for it he sacrificed his life like his father. The Safavid movement did not end with the death of their leaders' one after another, until Ismail was able to achieve the goal of his father and grandfather to establish a Shiite state. This research took the historical-chronological approach to reveal the events and how to change the doctrine method, and establishment of state, which consists of four axes. The first one dealt with up rise of political signs in changing the Safavid sect during the reign of Sultan Sheikh Ali Siyaposh (793-830 H/1392-1427 D). The second was devoted to talk about Sheikh Junaid and the beginning of the stage of political activity for the Safavid Order (864-851 H/1448-1459-60). The third took the title of progress of the Safavid movement during the era of Sheikh Haider (873 - 893 H/1468-1487 D). The fourth axis focused on the efforts and preparations of Safavids to establish the state (893-907 H/1487-1501 D).